On the A∞ [infinity symbol] conditions for general bases - Duoandikoextea, Javier (2016)
We discuss several characterizations of the A∞ class of weights in the setting of general bases. Although they are equivalent for the usual Muckenhoupt weights, we show that they can give rise to different classes of weights for other bases. We also obtain new characterizations for the usual A∞ weights.